1982
DOI: 10.1021/i200019a031
|View full text |Cite
|
Sign up to set email alerts
|

Fluosilicic acid extraction by high-molecular-weight amines

Abstract: The extractlon of fluoslilclc acid from dilute aqueous solutions by high-molecular-weight amines in kerosene has been studied. Extraction equlllbrium curves for various commercial amines are presented for room temperature, an amine concentration of 0.2 M, and aqueous acid concentrations up to 1 M. Formation of stable suspensions, coextraction of water, and aggregation of amine salts are discussed. Amine extraction of fluosilicic acid is compared with that of other mineral acids. The enthalpy, entropy, and equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Solvent extraction data have been presented (Tivnan and McCluskey, 1982) for HzSIF, with primary, secondary, tertiary and quaternary amines. They assumed the extracted species to be (R3NHt)2 SiFi-and presented equilibrium constants for this amine-salt formation.…”
Section: Literature Surveymentioning
confidence: 99%
See 4 more Smart Citations
“…Solvent extraction data have been presented (Tivnan and McCluskey, 1982) for HzSIF, with primary, secondary, tertiary and quaternary amines. They assumed the extracted species to be (R3NHt)2 SiFi-and presented equilibrium constants for this amine-salt formation.…”
Section: Literature Surveymentioning
confidence: 99%
“…Tivnan and McCluskey (1982) concluded that the extracted species was (R,NH'),SiFi-. Thus no limitations are imposed on the activity coefficients as defined in Equations (lo)-( 12).…”
Section: + V I 4 Initially the Value For B14 Was Taken From Bromleymentioning
confidence: 99%
See 3 more Smart Citations